GENERAL AND SPECIAL DISCIPLINARY RESPONSIBILITY - Zherebtsov, D. (Київський національний університет імені Тараса Шевченка, 2019)
The article is devoted to the study of legal regulation of disciplinary responsibility of employees. The expediency of separation of general and special disciplinary responsibility is substantiated. Specific features of special disciplinary responsibility are outlined. Proposals for improving national legislation providing for disciplinary liability are provided. In particular, it is proposed in all special laws that provide for disciplinary liability to clearly link all disciplinary penalties to specific disciplinary offenses. The peculiarities of disciplinary responsibility are presented, one of which is the use of penalties by the subject of employment relationship, namely the employer, which makes disciplinary responsibility one of the expressive powers of the employer in relation to the employee who has concluded an employment contract with him. The main differences between the special disciplinary responsibility and the general are noted, namely: 1) the circle of persons to whom it applies; 2) types of disciplinary sanctions; 3) the number of persons who may apply disciplinary sanctions; 4) the procedure for applying the penalties; 5) the procedure for appealing disciplinary penalties. It is substantiated that the special disciplinary responsibility of employees differs from the general broader content of disciplinary misconduct, more severe sanctions. An analysis of the national legislation was carried out, which allowed to identify a number of laws establishing the peculiarities of disciplinary responsibility. It is noted that all the above laws establish disciplinary liability only for a clearly defined circle of employees. Attention is drawn to the fact that although the aforementioned laws apply to public servants, they lack unanimity, above all in the amount of disciplinary sanctions that may be imposed on the employees concerned. It is proposed in all special laws that provide for disciplinary responsibility to clearly attach all disciplinary penalties to specific disciplinary offenses.

Стаття присвячена дослідженню правового регулювання дисциплінарної відповідальності працівників. Обґрунтовується доцільність виокремлення загальної та спеціальної дисциплінарної відповідальності. Окреслюються особливості спеціальної дисциплінарної відповідальності. Надаються пропозиції з удосконалення національного законодавства,  яке передбачає дисциплінарну відповідальність. Зокрема пропонується у всіх спеціальних законах, які передбачають дисциплінарну відповідальність, чітко прив’язати всі дисциплінарні стягнення до конкретних дисциплінарних проступків. Наведені особливості дисциплінарної відповідальності, однією з яких є застосування стягнень суб’єктом трудових правовідносин, а саме роботодавцем, через що дисциплінарна відповідальність є одним із виявів владних повноважень роботодавця стосовно працівника, що уклав із ним трудовий договір. Зазначаються основні відмінності спеціальної дисциплінарної відповідальності від загальної, а саме: 1) коло осіб, на яких вона поширюється; 2) види дисциплінарних стягнень; 3) коло осіб, які можуть застосовувати дисциплінарні стягнення; 4) порядок застосування стягнень; 5) порядок оскарження покладених дисциплінарних стягнень. Обгрунтовано, що спеціальна дисциплінарна відповідальність працівників відрізняється від загальної ширшим змістом дисциплінарного проступку, суворішими санкціями. Проведено аналіз національного законодавства, який дозволив виділити низку законів, які встановлюють особливості дисциплінарної відповідальності. Відзначено, що всі вищезазначені закони встановлюють дисциплінарну відповідальність лише для чітко визначеного в них кола працівників. Звернено увагу на те, що хоча вищезазначені закони стосуються службовців державних органів в них не має одностайності, передусім у кількості видів дисциплінарних стягнень, які можуть бути накладені на відповідних службовців. Запропоновано у всіх спеціальних законах, які передбачають дисциплінарну відповідальність чітко прив’язати всі дисциплінарні стягнення до конкретних дисциплінарних проступків
ЗАГАЛЬНА ТА СПЕЦІАЛЬНА ДИСЦИПЛІНАРНА ВІДПОВІДАЛЬНІСТЬ
Keywords: disciplinary responsibility; disciplinary misconduct; disciplinary action; labor discipline; work duties; reprimand; dismissal.; дисциплінарна відповідальність; дисциплінарний проступок; дисциплінарне стягнення; трудова дисципліна; трудові обов’язки; догана; звільнення.